Estudo da remoção de nitrogênio, com ênfase na volatização de amônia, em lagoas de polimento de efluentes de reatores UASB tratando esgotos urbanos de Belo Horizonte/MG - Fernando Augusto Lopes de Assuncao (2009)
This research evaluated the performance of three polishing ponds in series followed by a subsurface coarse rock filter treating the effluent from an Upflow Anaerobic Sludge Blanket (UASB) reactor, at demonstration scale, in the city of Belo Horizonte, Brazil,with emphasis on the investigation of the removal of nitrogen by ammonia volatilization. The system comprised three ponds in series: Ponds 1 and 2 operated with average depths of 0,80 m and Pond 3 with 0,60 m. The total hydraulic detention time was 10 days. In order to measure the volatized ammonia, an apparatus composed by a capturechamber and an absorption system (boric acid) was installed on the surface of the ponds. The air was inserted in the capture chamber and forced the headspace gases to bubble-up though a boric acid solution, thus absorbing the volatilized ammonia. The samples were then analyzed for NH4 + in the laboratory. The treatment system produced effluent with average concentrations of BOD, COD and TSS of 58 mg/L, 128 mg/L and 49 mg/L, respectively. The system showed an averageoverall efficiency of 50% in the removal of ammonia, and the effluent hadconcentrations lower than the target value of 20 mg/L during 80% of the study period. Under conditions of high temperature and pH, the effluent of system had lower concentrations of ammonia. There was an increase in the efficiency of the ponds with lower surface ammonia loading application rates. The rate of ammonia volatilization observed in the three polishing ponds was on average less than 0.2 kg/ha.d, representing less than 3% of the ammonia removed in the ponds. The results suggest that ammonia volatilization was not a predominant mechanism for nitrogen removal in the polishing ponds. Further studies related to the importance of other mechanisms in the removal of nitrogen, such as nitrificationfollowed by denitrification and nitrogen assimilation by the biomass with consequent detention in sludge, are necessary